Study of eosinophil count in nasal smear and peripheral blood smear in children with allergic rhinitis - Rudrappa, Sudha; Kumar, Rajendra; Kumar, Vinay (International Journal of Contemporary Pediatrics, 2019)
Background: Allergic respiratory disorders are the common cases seen in Pediatrics OPD. With an appropriate history and detailed examination, the diagnosis usually may not be problematic and routine investigations may not contribute much for the final diagnosis but may help in ruling other possibilities. The objectives of this study were done to know the eosinophil counts in nasal and blood smear and to assess the feasibility of nasal cytogram which is simple, economical and reliable investigation in patients of allergic respiratory disorders. Methods: A prospective clinical correlation study conducted in outpatient visiting Mysore Medical College and Research Institute, Cheluvamba hospital Department of Pediatrics and ENT Department KR hospital. 60 children of age group between 2 to 18 years were selected to estimate the eosinophil count in nasal and peripheral smear in allergic rhinitis. All allergic rhinitis cases based on clinical signs and symptoms were selected and investigated for nasal and blood eosinophilia. The nasal and blood eosinophilia were compared with each other and the clinical findings of allergic rhinitis were studied. Results: In this study peak age incidence is between 6-10 years and there is equal gender distribution. Seasonal variation and pollen allergens were the most common risk factors for allergic rhinitis. Running nose and the nasal obstruction were the most common symptoms in children with allergic rhinitis followed by sneezing and itching. One tenth of the children with allergic rhinitis had bronchial asthma. Nasal eosinophilia contributes to the diagnosis of allergic rhinitis as compared blood eosinophilia. Mild intermittent variety of allergic rhinitis was the most common form of allergic rhinitis. Conclusions: Among various risk factors for allergic rhinitis, seasonal variation and pollen allergens have significant association with the severity of allergic rhinitis. Among various symptomology, only itching had a significant relation to the severity of allergic rhinitis.